Involving Clients to Inform Development and Implementation of Combined Type 2 Diabetes and Chronic Kidney Disease Care Using Discovery Interview Technique - Blanchfield, Denise; O’Connor, Laserina (International Journal of Nursing Research, 2023)
Introduction: The development of chronic kidney disease in persons with Type 2 diabetes has been described as an epidemic. Standard outpatient care for these associated conditions is routinely provided separately, resulting in missed opportunities to implement preventative and early management strategies. Historically, care delivery for these combined conditions has fallen within the remit of medical professionals, evidenced by a dearth of information pertaining to the contribution of advanced practice nursing for this cohort. Clients report an uncoordinated impersonal approach to care delivery for associated conditions, however incorporating their experience is vital to the delivery of patient centered care and will be included in this study through their stories. The primary aim of this participatory action research (PAR) study is to utilize the client care stories and healthcare professional perspectives to inform development and implementation of a new combined Type 2 diabetes and chronic kidney disease service in the context of advanced practice nursing. Methodology: This study adopted a PAR approach informed by patient discovery interviews and key stakeholders focus groups. Transcripts will be developed from discovery interviews and focus groups and analyzed using thematic analysis. Results: The PAR will utilize thematic analysis outcomes to inform the primary aim and clinical outcomes from combined care will be evaluated after 9 months by retrospective chart review. Conclusion: The approach adopted in this study represents a departure from traditional medically led care strategies. Outcomes may elucidate potential challenges to the development and delivery of innovative care delivery for underserved patient cohorts in the context of advanced practice nursing.